Long-Term Tillage and Nitrogen Fertilizer Rates Effect on Grain Yield and Nitrogen Uptake in Dryland Wheat and Sorghum Production - M. Majrashi; A. K. Obour; C. J. Moorberg (Kansas Agricultural Experiment Station Research Reports, 2019)
Winter wheat and grain sorghum rotation is a common cropping system in dryland environments in western Kansas. A long-term field experiment (started in 1975) was conducted in Hays, KS, to examine interaction effects of tillage and nitrogen (N) fertilizer rates on wheat and grain sorghum yields, protein content, N uptake, and N use efficiency (NUE). The experimental design was a split-split-plot arrangement of rotation, tillage, and N application treatments in a randomized complete block design. The main plots were the crop phase (winter wheat, grain sorghum, or fallow), sub-plots were three tillage systems (conventional tillage (CT), reduced tillage (RT), and no tillage (NT)). The sub-sub-plots were four N rates (0, 20, 40, and 60 lb/a), which were modified in fall 2014 to 0, 40, 80, and 120 lb/a. Results showed year-to-year variability in winter wheat and grain sorghum responses to tillage practices and N fertilizer rates. Competition from herbicide-tolerant grass weeds reduced winter wheat yields in NT treatments in dry years but performed similarly to tillage treatments in wet years. However, grain sorghum yields with NT were greater or similar to CT or RT in most years of the study. Grain yields for both crops increased with N fertilizer application rates. Decreasing tillage intensity did increase wheat grain protein concentration only in 2018, which was relatively dry. Applying N fertilizer improved protein concentration, but the effect was more pronounced in years with less than average growing season precipitation. However, N use efficiency decreased at a higher N fertilizer rate particularly in dry years for both crops.
Keywords: conventional tillage; reduced tillage; no tillage; N fertilizer; N uptake; dryland systems